2022
DOI: 10.1002/acr.24862
|View full text |Cite
|
Sign up to set email alerts
|

Association of Healthy Lifestyle Behaviors and the Risk of Developing Rheumatoid Arthritis Among Women

Abstract: Objective. To investigate whether a healthy lifestyle, defined by a healthy lifestyle index score (HLIS), was associated with rheumatoid arthritis (RA) risk, overall and with seropositive/seronegative subtypes.Methods. We analyzed female nurses in the Nurses' Health Study (NHS, 1986(NHS, -2016 and NHSII (1991NHSII ( -2017. Lifestyle and medical information were collected on biennial questionnaires. Medical records confirmed incident RA and serostatus. The HLIS index includes 5 modifiable components: smoking, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
10
0
3
Order By: Relevance
“…A correct lifestyle is important for preventing both seropositive and seronegative RA. A recent study conducted on 1,219 incident RA cases (776 seropositive, 443 seronegative) demonstrated that a high level of healthy lifestyle index score was associated with a lower RA risk, both in seropositive and seronegative RA, with hazard ratios of 0.85 and 0.87, respectively (18). The healthy lifestyle index analysed 5 different aspects of lifestyle: smoking, alcohol consumption, body mass index, physical activity, and diet; the higher the index, the healthier the lifestyle.…”
Section: Lifestyle and Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A correct lifestyle is important for preventing both seropositive and seronegative RA. A recent study conducted on 1,219 incident RA cases (776 seropositive, 443 seronegative) demonstrated that a high level of healthy lifestyle index score was associated with a lower RA risk, both in seropositive and seronegative RA, with hazard ratios of 0.85 and 0.87, respectively (18). The healthy lifestyle index analysed 5 different aspects of lifestyle: smoking, alcohol consumption, body mass index, physical activity, and diet; the higher the index, the healthier the lifestyle.…”
Section: Lifestyle and Environmentmentioning
confidence: 99%
“…• Endogeneous and environmental factors contribute to disease pathogenesis, but specific risk factors could differ between seropositive and seronegative RA (18,19,22,23). • Differences in the pathogenic pathways between the two subsets of the disease can be partially captured from the analysis of the synovial tissue (29,30).…”
Section: Take-home Messagesmentioning
confidence: 99%
“…The effect of a high EDII on RA risk mentioned above was attenuated after adjusting for BMI [ 12 ]. In addition, a recent analysis of the NHS cohort revealed that obesity had the most marked effect on RA risk [ 4 ], and after adjustment for the BMI, the AHEI 2010 did not contribute independently to the hazard ratio for RA [ 4 ]. By analyzing the data of 108,000 women who were followed-up prospectively between 1989 and 2017, the NHS demonstrated that weight gain from baseline was quantitatively associated with the risk for seropositive and seronegative RA.…”
Section: Nutritional Factors For the Etiology And The Course Of Ramentioning
confidence: 99%
“…Recently, the Nurses Health Study (NHS) cohorts were analyzed with respect to the impact of modifiable lifestyle factors (cigarette smoking, being obese, lacking physical activity and consuming unhealthy diets, as well as drinking alcohol in excess) on the risk of RA. A healthy lifestyle index score (HLIS) was developed to quantify these five factors [ 4 ]. In general, a higher (healthier) HLIS was associated with a lower hazard ratio (HR) for RA, most prominently in women with five healthy lifestyle factors (HR 0.42), which was even lower for seropositive RA (HR 0.24) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation